Implementation of a Love-Based Curriculum in the Islamic Education to Foster Humanistic, Nationalistic, and Tolerant Character Traits in Students at MA Fathul Huda - Husen Sahab; Nur Cholid (Universitas Wahid Hasyim Semarang, 2026)
The growing phenomenon of dehumanization, intolerance, and moral degradation in educational settings indicates a gap between the goal of education as a means of character building and teaching practices that remain focused on cognitive aspects and formalities. This underscores the need for an educational model capable of balancing intellectual, emotional, spiritual, and social aspects. This study aims to analyze the implementation of the Love-Based Curriculum (KBC) in Islamic Religious Education (PAI) instruction and its implications for strengthening the humanistic, nationalistic, and tolerant character of students at MA Fathul Huda. This study employs a descriptive qualitative approach, utilizing data collection techniques such as observation, in-depth interviews, and document analysis, which are subsequently analyzed through data reduction, presentation, and conclusion drawing. The research findings indicate that the implementation of the Love-Based Curriculum (KBC) in Islamic Education (PAI) at MA Fathul Huda is effective in strengthening students’ humanistic, nationalistic, and tolerant character through a school culture rooted in compassion, social conditioning, teacher role modeling, and inclusive pedagogical relationships. Character development is evident in the growth of empathy, social awareness, mutual cooperation, respect for differences, and the creation of harmonious relationships among students and between students and teachers. These findings indicate that character development is more effectively fostered through a learning approach rooted in compassion and love.